PENINGKATAN PENGUASAAN KOSAKATA BAHASA INGGRIS MELALUI METODE BERMAIN KARTU BERGAMBAR TK BILINGUAL PONTIANAK TENGGARA - Yulita Yulita; Marmawi Marmawi; Halida Halida (Universitas Tanjungpura, 2017)
AbstractThis study aims to see the improved mastery of english vocabulary through methods of playing bilingual kindergarten picture card pontianak southeast. Based on the results of research and data analysis can be concluded: (1) Learning planning in improving vocabulary mastery The English language of children aged 5-6 years can be categorized as